Despite early Medicaid expansion, decreased durable virologic suppression among publicly insured people with HIV in Washington, DC: a retrospective analysis - Deborah Goldstein; W. David Hardy; Anne Monroe; Qingjiang Hou; Rachel Hart; Arpi Terzian; on behalf of the DC Cohort Executive Committee (BMC, 2020)
Abstract Background Despite widely available access to HIV care in Washington, DC, inequities in HIV outcomes persist. We hypothesized that laboratory monitoring and virologic outcomes would not differ significantly based on insurance type. Methods We compared HIV monitoring with outcomes among people with HIV (PWH) with private (commercial payer) versus public (Medicare, Medicaid) insurance receiving care at community and hospital clinics. The DC Cohort follows over 8000 PWH from 14 clinics. We included those ≥18 years old enrolled between 2011 and 2015 with stable insurance. Outcomes included frequency of CD4 count and HIV RNA monitoring (> 2 lab measures/year, > 30 days apart) and durable viral suppression (VS; HIV RNA < 50 copies/mL at last visit and receiving antiretroviral therapy (ART) for ≥12 months). Multivariable logistic regression models examined impact of demographic and clinical factors. Results Among 3908 PWH, 67.9% were publicly-insured and 58.9% attended community clinics. Compared with privately insured participants, a higher proportion of publicly insured participants had the following characteristics: female sex, Black race, heterosexual, unemployed, and attending community clinics. Despite less lab monitoring, privately-insured PWH had greater durable VS than publicly-insured PWH (ART-naïve: private 70.0% vs public 53.1%, p = 0.03; ART-experienced: private 80.2% vs public 69.4%, p < 0.0001). Privately-insured PWH had greater durable VS than publicly-insured PWH at hospital clinics (AOR = 1.59, 95% CI: 1.20, 2.12; p = 0.001). Conclusions Paradoxical differences between HIV monitoring and durable VS exist among publicly and privately-insured PWH in Washington, DC. Programs serving PWH must improve efforts to address barriers creating inequity in HIV outcomes.